Soro de leite e glicerina veiculados à água para borregos - Tassia Ludmila Teles Martins (2013)
Two experiments were made to determine the nutritive value of the milk and biodiesel by-product: whey and glycerin, respectively, for that digestibility and intake trials were made, as well as was determinate the nitrogen and energy balance. The levels of the byproducts zero; 5; 10; 15 e 20% for the whey and zero; 3; 6; 9 e 12% for the glycerin, in a randomly assignment design, with five repetitions by treatment. The animals with no inclusion of whey and glycerin were the same ones for both evaluations. It was showed that the dry matter intake in grams for body weight by animal was higher for the animals from the 5 and 10% levels of inclusion of whey. The protein, mineral, total carbohydrates and total digestible nutrients showed the same behavior of the dry matter intake and were higher for the animals of the 5 and 10% treatment. The increasing levels of whey did not alter any of the digestibility coefficients. The energy intake for the animals from the 5 and 10% levels of inclusion was higher than the other treatments; as for the digestible, metabolizable energy and energy balance were lower in the inclusion of 20% of whey in diet. The addition of whey improved the nitrogen balance. The energy and nitrogen balances were positive in all inclusions. The water intake, water intake in function of metabolic weight and related to the dry matter intake were not affected by the inclusion of whey. The water intake and the hydric balance showed a quadratic decreasing response. The inclusion of whey for the lambs should be near to 10% of the diet. The dry matter intake in grams and in function of the body weight was not affected by the different inclusions of glycerin. The mineral intake in function of the metabolic weight was higher for the 6% of addition of glycerin and the mineral intake in grams by day was also affected by all the inclusions. The 6% of inclusion of glycerin led to higher protein intake. The inclusion of glycerin in the rations led to a quadratic response for ether extract intake and for the mineral matter intake in function f metabolic weight. The digestibility coefficients of the nutrients evaluated were not affected by the increasing levels of glycerin. There were higher nitrogen retentions for the 0, 3 and 9% treatments and the same ones showed lower urinary losses of nitrogen. The energy and protein balance were positive in all the rations tested. The nitrogen balance was higher for the 0 and 9% levels of inclusion. The water intake in absolute, related to body weight, metabolic weight and related to the dry matter intake were not affected by the addition of the glycerin, as well as the hydric balance. Inclusion of glycerin in diets did not alter in the digestibility and intake of nutrients and the water intake. The glycerin can be added in levels until 12% in the diet.